Pengembangan E-Modul Berbasis Android Pada Mata Pelajaran Teknologi Jaringan Berbasis Luas (WAN) - Jayat Jayat; I Nyoman S. Degeng; Ibut Priono Leksono (Jurnal JEETech, 2023)
ABSTRACT Technology has an important role in realizing an innovative, creative and modern learning system, one of which is the E-module. This Android-based E-Module is a form of technological progress in education. The rapid development of technology encourages the replacement of printed modules and their presentation is transformed into electronic form, giving birth to a new term, namely electronic module or better known as E-module (Winatha, 2018). Development of Android-Based E-Modules in Broad-Based Network Technology Subjects for Class XI Vocational High School students the author did for the reason that students experienced difficulties in participating in learning. With the E-Module it is hoped that students can improve their learning methods, and help make it easier to understand the material before practice. The development of this E-Module is in the form of an application that will be more accessible. The model used in this study is the ADDIE Model (Analyze, Design, Development, Implementation, and Evaluation). Thus students who experience difficulties in participating in learning activities are expected to be able to improve their learning methods, increase student learning motivation on broad-based network technology competency standards (WAN) in the competence of Computer and Network Engineering expertise in Vocational High Schools. In addition, it is hoped that this E-Module can facilitate the lack of learning resources and help make it easier to understand the material before practice. ABSTRAK Teknologi memiliki peranan yang cukup penting untuk mewujudkan sistem belajar yang inovatif, kreatif dan modern salah satunya dengan adanya E-modul. E-Modul berbasis Android ini merupakan salah satu wujud dari kemajuan teknologi dalam pendidikan. Perkembangan teknologi yang semakin pesat mendorong tergantikannya modul cetak ditransformasikan penyajiannya ke dalam bentuk elektronik sehingga melahirkan istilah baru yaitu modul elektronik atau yang lebih dikenal dengan istilah E-modul (Winatha, 2018). Pengembangan E-Modul Berbasis Android Pada Mata Pelajaran Teknologi Jaringan Berbasis Luas (WAN) Siswa Kelas XI SMK penulis lakukan dengan alasan karena peserta didik yang mengalami kesulitan dalam mengikuti pembelajaran. Dengan adanya E-Modul diharapkan peserta didik dapat memperbaiki cara belajarnya, dan membantu mempermudah pemahaman materi sebelum praktek.Pengembangan E-Modul ini berupa aplikasi yang akan lebih mudah diakses. Model yang dipakai dalam penelitian ini ialah Model ADDIE (Analyze, Design, Development, Implementaion, dan Evaluation). Peserta didik yang mengalami kesulitan dalam mengikuti kegiatan pembelajaran diharapkan dapat memperbaiki cara belajarnya, meningkatkan motivasi belajar peserta didik pada standar kompetensi teknologi jaringan berbasis luas (WAN) pada kompetensi keahlian Teknik Komputer dan Jaringan di SMK. Selain itu diharapkan E-Modul ini dapat memfasilitasi minimnya sumber belajar dan membantu mempermudah pemahaman materi sebelum praktek.